Formation of Character Values of High School Students Through the Project to Strengthen the Profile of Pancasila Students in Driving Schools in Makassar City - Ananda, Cantika; Muhajir, Muhajir; Suardi, Suardi (JED (Jurnal Etika Demokrasi), 2024)
The P5 program is part of the formation of educational character in the independent curriculum, resulting from discoveries that strengthen the educational character in the previous curriculum. This research aims to find out how to form the character values of high school students through the project to strengthen the Pancasila student profile. Then, this research applies a mixed research method, which combines quantitative and qualitative approaches in one study or research program and critically reviews reality. The use of mixed methods aims to obtain a more comprehensive analysis of research problems through several stages in the research process. Qualitative data collection techniques include observation, interviews, and documentation, while quantitative data collection is carried out through questionnaires using Google Forms. This research is carried out through various stages designed to achieve research success. The result of this study is the formation of character through P5.